Phenotypic Analysis of Major Agronomic Traits in 1008 RILs from a Diallel of Early European Soybean Varieties. Issue 2 (31st January 2017) - Kurasch, Alena K.; Hahn, Volker; Leiser, Willmar L.; Starck, Norbert; Würschum, Tobias
Abstract : Soybean [ Glycine max (L.) Merr.] is the most important leguminous crop worldwide, but Europe is currently heavily dependent on soybean imports. A prerequisite for further expansion of soybean cultivation in Europe is the improvement of cultivars by breeding. In our study, 1008 F5:8 recombinant inbred lines derived from an incomplete half‐diallel cross of five early‐maturing European soybean varieties were evaluated in multilocation field trials for grain yield, thousand‐kernel weight, plant height, protein content, and oil content. We observed significant genotypic variances, high heritabilities ( h 2 > 0.7), and transgressive segregation for all traits. Our results further revealed complex relationships between grain yield, plant height, and maturity, but nevertheless indicated that breeding of adapted and high‐yielding varieties is feasible. By contrast, protein and oil content were not affected by maturity but were highly negatively correlated ( r ∼ −0.9). Our results suggest that, to maximize protein yield, the maximization of grain yield appears to be the most promising strategy for soybeans for feeding purposes, while the selection of lines with very high protein content may be advantageous for food‐grade varieties, especially for tofu production. Taken together, our results on the available phenotypic variation, variance components, heritabilities, and trait correlations can expedite soybean breeding targeted at Central Europe.